Practical ways to deal with the high burden of cardiovascular disease in hemodialysis patients - Lima, José Jayme Galvão de (2006)
Cardiovascular disease is the main cause of death among hemodialysis patients. Although uremia by itself may be considered to be a cardiovascular risk factor, a significant pro- portion of dialysis patients die because of cardiovascular disease not directly attributable to uremia. Indeed, many of the cardiovascular diseases and cardiovascular risk factors in these patients are common to those occurring in the general population and are amenable to intervention. Lack of proper medical care during the early stages of renal insufficiency and pres- ent-day dialysis routines, by failing to correct hypertension, hypervolemia and left ventricular hypertrophy in many patients, may also add to the cardiovascular burden. The author suggests that, in addition to early treatment and referral to a specialist, chronic renal failure patients should undergo intensive cardiovascular screening and treatment, and correction of cardiovascular risk factors based on guidelines established for the general population.